The Effect of Work-Life Balance on Psychological Well-Being of Working Women at Regional Public Hospital - Arlind Angelica Jozana Makandolu; Mernon Yerlinda Carlista Mage; Feronika Ratu (Universitas Nusa Cendana, 2026)
Soe Regional Public Hospital, the main referral hospital in South Central Timor Regency, faces a high workload along with limited family-friendly policies and psychosocial support. These conditions affect working women who perform dual roles, potentially influencing their psychological well-being. This study aimed to examine the effect of work–life balance on the psychological well-being of women at Soe Regional Public Hospital. A quantitative approach with simple regression analysis was applied to 60 married women aged 21–40 years using total sampling. Data were collected using work–life balance (Greenhaus et al., 2003) and psychological well-being scales (Ryff et al., 2004), and analyzed with SPSS. Results showed moderate work–life balance and fairly good psychological well-being. Regression analysis indicated a positive and significant effect (p < 0.05), with a contribution of 44.2%, while 55.8% was influenced by other factors.